COMPARISON OF THE PERALUMINOUS RARE-METAL’S GRANITES OF THE UKRAINIAN SHIELD AND THE NORTH-EASTERN PART OF THE BOHEMIAN MASSIF (ORE MOUNTAINS) - Tolstoy, M.; Kostenko, N. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
As a result of chemical and trace-element mapping of granites of the Ukrainian Shield and rare-metal granitoids of the Ore Mountains is determined by mathematical methods, that their direct analogs among the Ukrainian granites are granites of the kamennye mogily complex. It is assumed that a range of arrays of these rocks could have formed ore concentrations of tin.